“Бодончир мунхаг” нэрийн тухайд - Энхбат, Авирмэд (Historia Mongolarum, 2003)
In the 17th article of Secret History of Mongols there is written the name Bodonchir Munkhag. There are various descriptions and interpretation of this name. I have a hypothesis that Boorchi, the ancestor of Borgigon family, have got this name. The meaning of this name is a wise or hero which sumbolizes him as a wise king. Because at that times Mongols had a custom to use foreign words equal to meaning of Mongolian symbolizing the character of the person.